Involuntary resettlement and sustainable development conceptual framework, reservoir resettlement policies, and experience of the Yudongxia Reservoir. - Sapkota, Nogendra (East Asia working papers., 2017)
Development projects displace about 10 million people globally each year, and reservoir projects cause the most severe impacts. Involuntary resettlement is a complex issue, and requires sufficient knowledge, policies, and practices to manage it successfully, particularly in reservoir projects. The case study of the Yudongxia Reservoir in the PRC, a reservoir project financed by the Asian Development Bank which has 20 years of experience with dam and reservoirs projects in the PRC, shows successful overall results in compensation and resettlement of relocated people; although some rehabilitation measures showed mixed results. Find out how resettlement issues can be managed successfully through policies and practices in reservoir projects, focusing on sustainable development outcomes for relocated people.